Sto let PF Univerze v Ljubljani: slavnostna akademija in okrogla miza predsednikov dveh najvišjih evropskih sodišč - Zagorac, Dean (Javna uprava, 2021)
On the occasion of the 100th anniversary of the Faculty of Law of the University of Ljubljana, the Solemn Academy was organised, which took place on 27 May 2021 in the Gallus Hall of Cankarjev dom in Ljubljana. The head of the Programme and Organising Committee of the Solemn Academy was Professor Katja Škrubej. A series of events in honour of the centenary was concluded with the Solemn Academy, which began in October 2018 with the unveiling of a monument in the main faculty hall in memory of the formation of the first Slovenian government the SHS National Government in Ljubljana. On the same day, the Law Faculty International Forum, under the leadership of Professor Janez Kranjc, organised a round table discussion Challenges and Perspectives of the Highest European Courts, attended by the President of the Court of Justice of the European Union, Professor Koen Lenaerts, and the President of the European Court of Human Rights, Professor Robert Spano. The discussion was led by London attorney Shaheed Fatima QC and NYU professor Joseph H. H. Weiler. The round table discussion was held by videoconference.
Keywords: Court of Justice of the EU; ECtHR; Law Faculty of the University of Ljubljana; obletnice; Pravna fakulteta Univerze v Ljubljani; solemn academy